EFL students' views of willingness to communicate in the extramural digital context. Issue 7 (3rd September 2019) - Lee, Ju Seong
Abstract: This study examined factors that might have affected EFL learners' willingness to communicate (WTC) in the extramural digital (ED) environment, a rapidly emerging L2 communication context. The investigator conducted a semi-structured interview with 98 EFL students from three Korean universities. Drawing on grounded theory, socio-political (Korea's K-12 instruction), contextual (familiarity with interlocutors and communities), and individual variables (L2 self-confidence and anxiety) emerged as major sources of influence on participants' L2 WTC. Additionally, these sub-variables appeared to interact simultaneously during L2 communication in the ED context. This study contributes to further advancing our understanding of L2 WTC in a CALL environment. It also offers pedagogical insights into how L2 teachers can facilitate EFL learners' WTC in a range of extramural digital environments where their L2 WTC is very different from face-to-face classroom and extracurricular digital settings.